A Distinction Without a Difference? Good Advice for Moral Error Theorists1. (3rd October 2013) - Lillehammer, Hallvard
Abstract: This paper explores the prospects of different forms of moral error theory. It is argued that only a suitably local error theory would make good sense of the fact that it is possible to give and receive genuinely good moral advice.